Moisture ,Storage Capacities in, Relation of Textural L Composition of Western Rajasthan Soils - Kolarkar, A S; Singh, N (Annals of Arid Zone, 2016)
Two hundred soil samples were collected from various parts of Western Rajasthan and analysed for mechanical composition, moisture equivalent and water holding capacity. There are significant relationship between silt, clay silt+clay and these tow moisture constants. Silt has greatest effect on both of these moisture constants, clay being the next and silt + clay last.